Why Foot-and-Mouth Disease-Free with Vaccination Should Be Equivalent to Foot-and-Mouth Disease-Free without Vaccination - Moura, Pedro (2024)
Foot-and-Mouth Disease (FMD) is still one of the most relevant animal diseases and remains of global concern. The World Organization for Animal Health (WOAH) has specified two sanitary statuses that assure freedom from FMD: a country or zone can be free from FMD either with or without vaccination. To obtain either of the two statuses, absence of virus circulation must be shown. The standards set by WOAH are used for trade negotiations. During recent decades, different tools and approaches were developed to control FMD, including vaccines, diagnostics, and the Progressive Control Pathway for FMD. These tools improved over time, and nowadays highquality, reliable vaccines and specific diagnostics are available to efficiently control and detect the infection, even in vaccinated populations. Due to these improvements, it is no longer justifiable to treat the two FMD-free statuses differently. The distinction between the statuses provides wrong incentives and tempts countries to take increased risks by stopping vaccination to improve their trade conditions, which can have potentially devastating consequences. The decision to stop vaccination should only be made on the basis of a careful and comprehensive analysis of the local and regional epidemiological situation. This paper presents the perspective that member countries and WOAH should recognize the two FMD-free statuses as equivalent.